2012
DOI: 10.5296/ijl.v4i4.2318
|View full text |Cite
|
Sign up to set email alerts
|

SMS Vocabulary Learning: A Tool to Promote Reading Comprehension in L2

Abstract: Reading comprehension and vocabulary knowledge have critical roles in success in a foreign language. They have also intricate relationships so that the increase in one leads to increase of the other. The aim of the present study was to investigate the effect of learning vocabulary via SMS -as an optimal way of teaching words-on university students reading comprehension. To this end, 45 freshmen students took part in this study. They were assigned as experimental and control group. Before the beginning of the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 15 publications
(19 reference statements)
1
12
0
Order By: Relevance
“…[3][4][5][6] Recently work on computer assisted language learning (CALL) and mobile assisted language learning (MALL) has taken a great leap in the realm of second language acquisition. [6][7][8][9][10] However, since the mid-2000s robots have also been explored as helpful and innovative tools that have come to the aid of language teaching and learning. [11][12][13][14] The work presented here focuses on the study of the adaptable social, interactive, and cognitive aspects of robot behavior in an assistive context designed for young students/individuals seeking to learn English as a 2nd language.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6] Recently work on computer assisted language learning (CALL) and mobile assisted language learning (MALL) has taken a great leap in the realm of second language acquisition. [6][7][8][9][10] However, since the mid-2000s robots have also been explored as helpful and innovative tools that have come to the aid of language teaching and learning. [11][12][13][14] The work presented here focuses on the study of the adaptable social, interactive, and cognitive aspects of robot behavior in an assistive context designed for young students/individuals seeking to learn English as a 2nd language.…”
Section: Introductionmentioning
confidence: 99%
“…However, recently more attention has been paid to the investigation of incidental and intentional learning of vocabulary, 16 use of visuals for better retention, 17,18 application of computer in vocabulary learning/teaching, and the use of MALL for vocabulary learning. [7][8][9][10] Nonetheless, very few studies have attempted to design and evaluate vocabulary learning with the help of a robot. 13 Their study concentrated on vocabulary development of a toddler and no studies have focused on the vocabulary learning and retention of junior/high school students using robotics technology thus far.…”
Section: Introductionmentioning
confidence: 99%
“…Many researches have indicated that learners' attitudes are important in the use of social networking applications in their language learning practices (e.g., Alemi & Lari, 2012;Dashtestani, 2016;Liaw et al, 2007;Ma'azi et al, 2018;Manca & Ranieri, 2017;Rahimi & Yadollahi, 2011;Soltani Tehrani & Tabatabaei, 2012). All these studies showed that students had positive attitudes towards the application of online social networks in English classes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, this leaves teachers, material developers, and educators trying to keep up with the dramatic development of multimedia technology. With the advancement and growth of computers and mobile devices, Computer Assisted Language Learning (CALL) and Mobile Assisted Language Learning (MALL) have gained attention for second language educational theories for over fifteen years [16][17][18][19][20]. The use of computers in the English language classrooms and laboratories is known to be useful for both teachers and learners.…”
Section: Background and Historymentioning
confidence: 99%
“…This method offers the EFL learners a chance to practice writing on-the-move. It further provides an on-line and quick tool to write and share ideas, thoughts, and correspond instantly with the person on the other side [16][17][18][19].…”
Section: 3writing and Technologymentioning
confidence: 99%